262 Immunological pathways in systemic lupus erythematosus disease manisfestaion: cerebral lupus. (April 2019) - Fewings, Nicole L; Swaminathan, Sanjay; Booth, David; Lin, Ming Wei
Abstract : Background: Multiple organ systems including skin, musculoskeletal, neurological, renal and hematologic systems can be involved in patients with SLE. To date extensive research has been conducted to identify unique gene expression signatures using heterogeneous SLE cohorts, however little research has been conducted to delineate SLE signatures in patients with less common disease manifestations, such as cerebral lupus. The diagnosis and monitoring of patients with cerebral lupus is particularly challenging as traditional markers of lupus disease activity in peripheral blood are often negative, and the clinical symptoms overlap with many other non-immunological diseases. The aim of this study was to identify and interrogate immunological pathways that may be aberrant in this particular SLE disease subtype. Methods: Whole blood RNA was extracted from 46 SLE patients, 5 Autoimmune encephalitis and 20 healthy controls. Gene expression was measured using a Nanostring nCounter mRNA expression assay incorporating over 500 immunological genes. Data was analysed using Partek Genomics Suite to identify differentially expressed genes and find pathways that may be of interest to interrogate further in the context of SLE disease manifestations. Results: Clear differences in gene expression between healthy controls and SLE patients were evident. In our cohort of 46 SLE patients, seven had symptoms of cerebral lupus (seizure and/or psychosis). Cerebral lupus patients showed significantly different expression in 5 genes. TNFRSF1B, CD14 and IL1B expression was increased in cerebral lupus compared to other SLE, while PSMB7 and IKBKB was decreased in cerebral lupus compared to other SLE. Conclusions: The differences observed in this group of genes (CD14, PSMB7, IKBKB, IL1B and TNFRSF1B) implicate myeloid cell dysfunction as a possible point of difference between cerebral lupus and other forms of SLE. This preliminary finding may help explain the overlap between the innate and the adaptive immune dysregulation in lupus pathogenesis, and the use of TNF inhibition acutely in patients with a similar autoimmune cerebral disease, cerebral vasculitis. Funding Source(s): None